2019
DOI: 10.1212/wnl.0000000000007581
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of highly effective contraception use by women with epilepsy

Abstract: ObjectiveTo determine (1) the proportion of women with epilepsy (WWE) at risk of unintended pregnancy who use highly effective contraception, (2) demographic predictors, and (3) folic acid (FA) use.MethodsThese cross-sectional data come from 311 US WWE, 18–47 years, who participated in the Epilepsy Birth Control Registry (EBCR) web-based survey in 2017. They provided demographic, epilepsy, antiepileptic drug (AED), contraceptive, and FA data. We report frequencies of highly effective contraception use and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Nearly 30% did not use highly effective contraception methods and an additional 7% used hormonal contraception while on an enzyme-inducing antiseizure medication posing a risk of contraceptive failure. Older age, insurance coverage, and increased income were associated with highly effective contraceptive use [4]. This highlights the importance of counseling about contraception and pregnancy early.…”
Section: Contraceptionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nearly 30% did not use highly effective contraception methods and an additional 7% used hormonal contraception while on an enzyme-inducing antiseizure medication posing a risk of contraceptive failure. Older age, insurance coverage, and increased income were associated with highly effective contraceptive use [4]. This highlights the importance of counseling about contraception and pregnancy early.…”
Section: Contraceptionmentioning
confidence: 88%
“…Children exposed to antiseizure medication had increased risk of language impairment and delay but folic acid had a protective effect on language development [51,52 ]. Of note, the EBCR survey of more than 300 WWE found that only around 50% were taking folic acid [4]. Data from the NEAD study was retrospectively analyzed to evaluate if folic acid fortification in food was sufficient to increase childhood IQ.…”
Section: Folic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Epilepsy Birth Control Registry’s web-based survey, 33.6% of WWE did not use highly effective contraception. 16 …”
Section: Contraception Considerations For Wwementioning
confidence: 99%
“…24 Studies have shown that there is a need for more education and increased awareness regarding highly effective contraceptive methods in WWE. 25 Emphasis should be laid on the selection of contraception through a shared decisionmaking process with focus on a method with minimal interactions with patients' medication regimen and one that does not risk an increase in seizure frequency. Adolescents should be offered preconceptual counseling early in the course, and continued education should be undertaken after transitioning to adult health care.…”
Section: Effective Contraception Selection and Counselingmentioning
confidence: 99%